2000
DOI: 10.1083/jcb.149.2.397
|View full text |Cite
|
Sign up to set email alerts
|

The F-Box Protein Rcy1p Is Involved in Endocytic Membrane Traffic and Recycling Out of an Early Endosome in Saccharomyces cerevisiae

Abstract: In Saccharomyces cerevisiae, endocytic material is transported through different membrane-bound compartments before it reaches the vacuole. In a screen for mutants that affect membrane trafficking along the endocytic pathway, we have identified a novel mutant disrupted for the gene YJL204c that we have renamed RCY1 (recycling 1). Deletion of RCY1 leads to an early block in the endocytic pathway before the intersection with the vacuolar protein sorting pathway. Mutation of RCY1 leads to the accumulation of an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
185
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 159 publications
(197 citation statements)
references
References 64 publications
(127 reference statements)
12
185
0
Order By: Relevance
“…Eight had mutations in genes identified since 1996 as being involved in trafficking (VPS53, VAC7, VAM6, APM3, SYS1) or glycosylation (ALG12, ALG9, ROT2), providing multiple internal controls of the validity of our approach. Two (TLG2, RCY1) were identified within the EUROFAN secretion node simultaneously by our Western immunoblotting approach, and by screening for defects in fluid-phase endocytosis, and we have reported the initial characterization of these mutants (Séron et al, 1998;Wiederkehr et al, 2000). One gene (MON2) was identified within the EUROFAN secretion node by the drug sensitivity approach (Muren et al, 2001).…”
Section: Overview Of the Screeningmentioning
confidence: 99%
See 4 more Smart Citations
“…Eight had mutations in genes identified since 1996 as being involved in trafficking (VPS53, VAC7, VAM6, APM3, SYS1) or glycosylation (ALG12, ALG9, ROT2), providing multiple internal controls of the validity of our approach. Two (TLG2, RCY1) were identified within the EUROFAN secretion node simultaneously by our Western immunoblotting approach, and by screening for defects in fluid-phase endocytosis, and we have reported the initial characterization of these mutants (Séron et al, 1998;Wiederkehr et al, 2000). One gene (MON2) was identified within the EUROFAN secretion node by the drug sensitivity approach (Muren et al, 2001).…”
Section: Overview Of the Screeningmentioning
confidence: 99%
“…Later analysis showed that this gene was involved in a recycling pathway, as shown by the exit of the vital dye FM4-64, following its internalization by endocytosis. This new recycling pathway is thought to involve sorting from endosomes (possibly early or 'sorting' endosomes) back to the trans-Golgi network (TGN) (Wiederkehr et al, 2000). Rcy1p is located in zones of active polarized membrane growth (Galan et al, 2001).…”
Section: Deletions That Directly or Indirectly Impair Golgi Glycosylamentioning
confidence: 99%
See 3 more Smart Citations